Adubação com silício e tolerância ao déficit hídrico em cana-de-açúcar - Bezerra, Breno Kennedy Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Although the Brazilian sugar and ethanol industry has been facing one of its worst crises, sugarcane crop has been expanding to new areas, including sandy soils subject to water deficit. Silicon (Si) is an element that can minimize the effects of drought in several plants, but there is little information on its effects on sugarcane subjected to water deficit. Thus, the objective of this study was to evaluate the use of silicon fertilization in two sugarcane cultivars under water deficit during phase (tillering and maximum development). The two experiments were carried out inside a greenhouse at Agency for Agribusiness Technology of São Paulo (APTA), Piracicaba, SP, where were transplanted pre-sprouted seedlings in pots of 100 L. The design was randomized blocks with triple factorial 2x2x2 (variety, silicon and water regime) with four replications. Two varieties of sugarcane (drought tolerant -RB867515 and as sensitive-RB855536), with and without silicon-supplied (600 and 0 kg ha-1) subjected or not to water restriction (60% and 100% humidity of field capacity, respectively) this condition was imposed for 30 and 60 days during the tillering phase or maximum development phase (three and six months after transplanting) were studied. Evaluations were done at three periods: before water deficit and after 30 and 60 days. The effects in biochemical attributes (plant height, number of tillers, total leaves and green leaves) and physiological (SPAD index, electrolyte leakage, chlorophyll a and b content, specific leaf mass, leaf relative water content and leaf water potential) were studied. Si increased morphological development, by increasing on number of total leaves and tillers during tillering phase and increasing on number of total leaves, tillers and plant height on maximum development phase, on both varieties. There was effect of ...

Embora o setor sucroalcooleiro brasileiro enfrente, atualmente, uma de suas piores crises, a cultura da cana-de-açúcar continua em expansão para novas áreas, inclusive em solos arenosos sujeitos à deficiência hídrica. O silício (Si) é um elemento capaz de minimizar os efeitos do déficit hídrico em várias plantas, mas poucas são as informações sobre seus efeitos em cana-de-açúcar sob déficit hídrico. Assim, o objetivo foi avaliar os efeitos da adubação silicatada em duas variedades de cana-de-açúcar submetidas ao déficit hídrico em duas épocas (perfilhamento e máximo desenvolvimento). Foram conduzidos dois experimentos em casa-de-vegetação na área experimental da APTA Regional Polo Centro Sul, Piracicaba (SP) em vasos (100 L). O delineamento foi em blocos casualizados em arranjo fatorial triplo 2x2x2 (variedade, silício, regime hídrico) com quatro repetições. Foram estudadas duas variedades de cana-de-açúcar (tolerante - RB867515 e sensível à seca - RB855536), com e sem o fornecimento de Si (600 e 0 kg ha-1) e com e sem restrição hídrica (60% e 100% da umidade na capacidade de campo, respectivamente), condição esta imposta durante o perfilhamento ou no máximo desenvolvimento (três e seis meses após o transplantio). As avaliações foram feitas em três períodos: antes da imposição do déficit hídrico e após 30 dias e 60 dias. Foram estudados os efeitos nos atributos morfológicos (comprimento de plantas, número de perfilhamento, folhas totais e verdes) e fisiológicos da planta (índice SPAD, extravasamento de eletrólitos, conteúdo de clorofila a e b, massa foliar específica, teor relativo de água na folha e potencial de água foliar). O Si favoreceu o desenvolvimento morfológico das plantas, conferindo maior número de folhas totais e perfilhos na fase de perfilhamento e maior número de folhas totais, perfilhos e comprimento de ...
Silicon fertilization and the water deficit tolerance in sugarcane
Keywords: Cana-de-açúcar - Adubação; Silício na agricultura; Irrigação com déficit hídrico; Cana-de-açúcar